Enhancement of optical absorption in LT-GaAs by double layer nanoplasmonic array in photoconductive antenna. (December 2017) - Bashirpour, Mohammad; Kolahdouz, Mohammadreza; Neshat, Mohammad
Abstract: At the moment, weak optical absorption and small photocurrent of the terahertz photoconductive antennas (PCA) have forced scientific community to design and develop antennas with higher efficiencies. In this work, a novel configuration consists of a double layer nanodisk arrays has been proposed and thoroughly investigated. These arrays are able to couple the plasmon resonance to terahertz PCAs. The finite difference time domain (FDTD) method has been used to extract the characteristics of the proposed structure. The simulation results have indicated that the absorption of the proposed structure increase to more than 76% as compared to around 31.5% for conventional structures without any nanostructure and 46% for one layer nanoplasmonic structure in 800 nm wavelength. Optimized one layer nanoplasmonic array increases photocurrent up to 10.1 nA that indicates1022% enhancement in comparison with conventional structure. Using the double layer nanoplasmonic array results in 144% light absorption enhancement, and 3433% photocurrent enhancement in comparison with the conventional structure. Highlights: Terahertz photoconductive antennas with relatively high efficiencies have been designed. The FDTD method has been used to extract the characteristics of the proposed PCAs. The absorption of the proposed PCA is 76% at 800 nm compared to 31.5% for conventional PCAs. The photocurrent enhancement of 3433% compared with the conventional PCAs has been achieved.